Analysis of Knowledge and Attitudes of Pregnant Women towards Motivation to do the PMTCT VCT Test in the District Bojonegoro - Meika Sri Suryanti Fitriana; Byba Melda Suhita; Yenny Puspitasari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Transmission of human immunodeficiency virus (HIV) from mother to baby is now increasing with the increase in women infected with HIV. This study aims to analyze the knowledge and attitudes of pregnant women towards motivation to conduct PMTCT VCT test in Bojonegoro Regency. This research was carried out in five puskesmas in Bojonegoro, namely Ngambon, Sugihwaras, Kesongo, Malo and Kepohbaru Puskesmas. The study design was cross sectional study. The sampling technique used porpotional sampling and a sample of 110 respondents, where data collection was carried out using a questionnaire. Statistical tests used logistic regression tests at the significance level of p <0.05 and a 95% Confidence Interval (IK). The results showed that nearly half of the respondents 47,3% had good knowledge about HIV / AIDS and the PMTCT VCT test tended to have strong motivation at 62%. Statistically variable knowledge and attitudes of pregnant women have a significant relationship when a logistic regression analysis was performed with sig values. 0,000 which means the value is < 0.05. So that the knowledge and attitudes of pregnant women about HIV / AIDS, HIV VCT and PMTCT are considered influential on motivation to carry out VCT PMTCT tests.